1973
DOI: 10.1085/jgp.62.4.473
|View full text |Cite
|
Sign up to set email alerts
|

A Relaxation Oscillator Description of the Burst-Generating Mechanism in the Cardiac Ganglion of the Lobster, Homarus americanus

Abstract: Properties of the neural mechanism responsible for generating the periodic burst of spike potentials in the nine ganglion neurons were investigated by applying brief, single shocks to the four small cells with extracellular electrodes placed near the trigger zones of the small cells. The shock elicited a burst if presented during the latter portion of the silent period, terminated a burst during the latter portion of the burst period, and was followed by a newly initiated burst during the early portion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…(Early work in both the Maine lobster, Homarus, and the spiny lobster, Panulirus, is reviewed in Maynard, 1960;Hagiwara, 1961. More recent works are Cooke, 1966;Hartline, 1967 a, b;Connor, 1969;Hartline and Cooke, 1969;Mayeri, 1969 a, b;Rao et al, 1969;Van der Kloot, 1970;Anderson and Cooke, 1971;Tazaki, 1971 a, b;Livengood and Kusano, 1972;Mayeri, 1973. ) Though the ganglion contains only nine neurons, its integrative mechanisms are complex.…”
Section: Introductionmentioning
confidence: 99%
“…(Early work in both the Maine lobster, Homarus, and the spiny lobster, Panulirus, is reviewed in Maynard, 1960;Hagiwara, 1961. More recent works are Cooke, 1966;Hartline, 1967 a, b;Connor, 1969;Hartline and Cooke, 1969;Mayeri, 1969 a, b;Rao et al, 1969;Van der Kloot, 1970;Anderson and Cooke, 1971;Tazaki, 1971 a, b;Livengood and Kusano, 1972;Mayeri, 1973. ) Though the ganglion contains only nine neurons, its integrative mechanisms are complex.…”
Section: Introductionmentioning
confidence: 99%
“…When the electric shock was applied during the latter part of the burst, it terminated the burst . Mayeri (1973) also measured the threshold (minimal shock duration needed to evoke a burst) during the quiescent period . He found that from the time where a burst could be evoked, the threshold declined throughout the quiescent period .…”
Section: Discussionmentioning
confidence: 99%
“…Their famous system for which they obtained the Noble prize in "Physiology or Medicine" in 1963 (nobelprize.org) was later reduced to a system of two dynamic variables called Fitzhugh-Nagumo model [18,19] which represents a relaxation oscillator. A relaxation oscillator description of the burst-generating mechanism in the cardiac ganglion cells of the lobster was later developed by Mayeri [20]. Oscillations in cortical neurons were also modelled by Wilson-Cowan polynomial equations which model interactions between excitatory and inhibitory neurons [21][22][23][24].…”
Section: Biologically Inspired Neural Oscillatorsmentioning
confidence: 99%